Pengaruh Model Problem Based Learning Bermuatan Potensi Lokal Garam Krosok Terhadap Literasi Sains - Baren Mamora; Didik Setyawarno (Journal of Progressive Science Education, 2026)
The low level of scientific literacy among junior high school students remains a significant issue in science learning, which is generally teacher-centered, leading students to memorize concepts without understanding their application in everyday life. One effort to improve scientific literacy is through the implementation of the Problem-Based Learning (PBL) model integrated with local potential, such as krosok salt, making learning more contextual and meaningful. This study aims to describe the effect of implementing a Problem-Based Learning model incorporating the local potential of krosok salt on the scientific literacy of junior high school students. The research employed a quantitative method with a quasi-experimental design, specifically a nonequivalent control group design, involving an experimental class and a control class at SMP Negeri 7 Yogyakarta. The research instrument was a scientific literacy test that had been validated and tested for reliability. Data analysis was conducted using normality tests, homogeneity tests, independent sample t-tests, and effect size calculations to determine the magnitude of the treatment effect. The results showed that the significance value of the pretest data was 0.522, indicating no difference in initial ability between the two classes. Furthermore, the posttest data yielded a significance value of 0.025 (< 0.05) with an effect size of 0.594, which falls into the medium category. These findings indicate that the implementation of the Problem-Based Learning model integrated with the local potential of krosok salt has a positive effect on improving students’ scientific literacy. Therefore, this model is appropriate to be used as an alternative approach to contextual and meaningful science learning.